Professional Training of Future Masters of Preschool Education for the Formation of Engineering Skills of Preschoolers - Diachenko, Natalia (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article is devoted to the theoretical substantiation of the expediency of preparing future masters of preschool education for the formation of engineering skills in preschool children; analysis of scientists’ research on the problem of students’ readiness for pedagogical activity. Some issues of training future masters of preschool education to organize the formation of engineering skills in preschoolers as a necessary component of future professional activity are presented. The readiness of future masters for the formation of engineering skills is interpreted as a special new component in the personality structure, which determines the direction and nature of professional and pedagogical activities, its focus on engineering training of preschool children, consistent actualization in emotional and volitional acts and relevant means of engineering. Innovative ways to improve the professional training of future specialists in the field of preschool education at the second (master's) level are identified, taking into account the formation of competencies defined in the educational and professional training program for masters of specialty 012 Preschool education. Methodical recommendations for future masters of preschool education on the formation of engineering skills in preschool children are given. The essence of engineering thinking is determined as well as the ways of its formation and development in preschool children in the process of relevant activities. LEGO-design and other types of technical creativity are highlighted. The algorithm of formation of engineering skills in children is singled out, which, according to the author, is carried out in stages: "I am a researcher", "I am a designer", "I am a specialist", "I am an artist". The system principles of cooperation of the preschool institution with parents for future masters of preschool education on the formation of engineering skills in preschool children are highlighted.